Micropillar Compression of MoSi2 Single Crystals. Issue 1760 (13th January 2015) - Nakatsuka, Satoshi; Kishida, Kyosuke; Inui, Haruyuki
ABSTRACT: Deformation behavior of MoSi2 has been studied by micropillar compressions of single crystalline specimens prepared by focused ion beam (FIB) technique as a function of crystal orientation at room temperature. Activation of the 011<100> and 01 3 <331> slip systems were observed in the micropillars compressed along [ 1 10] and [0 15 1], respectively. The CRSS values for each slip system exhibit an approximate power law relationship with the edge length of micropillar. The 01 3 <331> slip exhibit much stronger size-dependence than the 011<100> slip system.